Protein level varicus tissues of the prawn, Penaeus merguiensis De Man (Crustacea decapoda,penaeidae) at different stages of ovarian maturation - Mohamed Kamil Abdul Rashid (Fakulti Pengajian Maritim dan Sains Marin, 2011)
The gonadosomatic indices (GSI) of forty penaeid prawns, Penaeus merguiensis at different stages of ovarian maturation were determined and found to be significantly different(P < 0.05). Analyses of protein levels in their ovaries and midgnt glands showed an increase in the ovary (10 -85 mg/g tissue) and a decrease in the midgnt gland (353 - 195 mg/g tissue), with ovarian maturation.